Emerging electrochemical tools for microplastics remediation and sensing - Martic, Sanela; Tabobondung, Meaghan; Gao, Stephanie; Lewis, Tyra (Frontiers in Sensors, 2022)
Microplastics are part of our daily lives and persist in the environment all across the globe. As a recently recognized emerging pollutant, there is a call to action to mitigate and monitor microplastics. Despite traditional remediation and characterization methodologies, MP-related challenges still exist. Electrochemical strategies for microplastic remediation have been reported in recent years, but very few reports exist on using electrochemical sensors for monitoring microplastics. Therefore, this mini review highlights the opportunities within the existing electrochemical remediation platforms towards sensor design and development, and elaborates on microplastic electrochemical sensors so far.